Dubbing Method and Learning Videos for Improving Students' English Speaking Skills - Erni Widiya Sari; Maulidiyyatul Uswah (Jurnal Langua, 2026)
This study investigates the effectiveness of the dubbing method combined with learning videos in improving students' English speaking skills, with particular attention to vocabulary, grammar, and pronunciation. The research employed a descriptive, pre-experimental design involving a single group assessed before and after the intervention. Participants were 44 second-semester students majoring in English Language and Literature at Bung Hatta University. Data were collected through observation, interviews, and recordings, and were categorized into five proficiency levels: unsatisfactory, fair, good, very good, and excellent. The pre-test results showed that most students fell into the fair and good categories, with seven students classified as unsatisfactory and none reaching the excellent level. After the dubbing technique was implemented using short instructional videos, the post-test results indicated significant improvement: no students remained in the unsatisfactory category, the number of students in the very good category rose from three to seventeen, and one student achieved the excellent category for the first time. These findings demonstrate that the dubbing method, supported by educational videos, effectively enhances students' speaking accuracy, fluency, vocabulary mastery, and pronunciation. Further research involving a larger and more diverse sample, along with a control group, is recommended to strengthen and generalize these findings.